2012
DOI: 10.1021/la301030f
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of the Swelling and Hydrolysis of a Single Crystalline Cellulose Fiber Catalyzed by Cellulase 7B from Trichoderma reesei

Abstract: The biodegradation of cellulose involves the enzymatic action of cellulases (endoglucanases), cellobiohydrolases (exoglucanases), and β-glucosidases that act synergistically. The rate and efficiency of enzymatic hydrolysis of crystalline cellulose in vitro decline markedly with time, limiting the large-scale, cost-effective production of cellulosic biofuels. Several factors have been suggested to contribute to this phenomenon, but there is considerable disagreement regarding the relative importance of each. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 38 publications
7
43
0
1
Order By: Relevance
“…1 A ). In situ AFM imaging shows that homogeneous substrate areas, corresponding to amorphous cellulose, are degraded to bare crystalline nanofibrils and crystallite surfaces with a defined and highly ordered structure (crystalline cellulose), comparable to AFM images of crystalline model substrates and fibrils (28, 43). Generally, we observed that large crystallites were degraded extremely slowly.…”
Section: Resultsmentioning
confidence: 66%
“…1 A ). In situ AFM imaging shows that homogeneous substrate areas, corresponding to amorphous cellulose, are degraded to bare crystalline nanofibrils and crystallite surfaces with a defined and highly ordered structure (crystalline cellulose), comparable to AFM images of crystalline model substrates and fibrils (28, 43). Generally, we observed that large crystallites were degraded extremely slowly.…”
Section: Resultsmentioning
confidence: 66%
“…Real-time AFM imaging has revealed the selective hydrolysis of the hydrophobic faces of bacterial cellulose by this exo-cellulase. The action of endoglucanase CeL7B on cellulose architecture was also recently investigated by real-time AFM [27] yielding similar results.…”
Section: Discussionmentioning
confidence: 70%
“…Wang et al [27] have visualized by AFM the topographic changes caused by Cel6A, including the swelling of the crystalline microfibrils and its capacity to expose single microfibrils.…”
Section: Introductionmentioning
confidence: 99%
“…7 and 8). In general, very few studies concerning the visualization of cellulase activity by the different microscopy techniques available (electron microscopy or probe microscopy) can be found in literature (Ding et al 2001;Lee et al 2000;Wang et al 2012). Besides, most of the published work deals with exoglucanases, particularly celobiohydrolase I (CBHI) acting on pure cellulose substrates.…”
Section: Discussionmentioning
confidence: 99%